The Forgotten Fruit: A Case for Consuming Avocado Within the Traditional Mediterranean Diet - Ford, Nikki A.; Liu, Ann G. (Frontiers in Nutrition, 2020)
The Mediterranean diet is rich in fruits and vegetables and includes an abundant intake of oleic-acid-rich olive oil. People who adhere to a Mediterranean diet have reduced risk for numerous chronic diseases. As obesity rates rise globally, people who choose to follow a traditional Mediterranean diet and/or make improvements in food choices may reduce their risk of metabolic dysfunction and disease. Incorporating non-traditional fruits and vegetables into the Mediterranean diet could provide greater flexibility in suitable food choices for people who struggle to adhere to recommended healthy dietary patterns, and it could also provide greater adaptability for people living outside of the Mediterranean region who are interested in adopting the diet. The avocado fruit thrives in a Mediterranean climate, is produced in the region, and is rich in oleic acid and fiber, yet avocados are not commonly consumed within the traditional Mediterranean diet. Based on the existing research studies on the health benefits of avocado consumption and the continued investigation into the nutritional attributes of the avocado, a case can be made for including avocados as part of the Mediterranean dietary pattern.